GRAMMATICAL ERROR MADE BY THE STUDENTS OF UKI TORAJA IN TRANSLATING INDONESIA-ENGLISH TEXT - matius tandi kombong (UKI TORAJA, 2015)
This research aimed to describe the error analysis by using translation test. This technique used in translating test which I focused on the analysis of the students’ error production in translating. This research formulates four objectives: 1.To find out the types of errors that the students make in translating sentences from Indonesian into English 2.To find out the most frequent errors made by the students of UKI Toraja 3. To find out the differences in number of grammatical errors made the students of UKI Toraja. The method used was descriptive method. The population of this research was the students of UKI Toraja academic year 2014/2015. The fourth semester students consist of 270 as population in this research. There were 30 students as sample in this research was taken from 270 students. The sixth semester students consisted of 270 students as a population in this research and there were30 students as sample of this research was taken from 270 students. It was taken by using cluster random sampling. Data and analysis of this research are the students’ translation from Indonesian text into English text.